Hoof Pressure Distribution Pattern of Blue Sheep During Walking on Different Slopes: A Subject-Specific Analysis - Liu, Xiangyu; Kui, Hailin; Qian, Zhihui; Ren, Lei (Frontiers in Veterinary Science, 2021)
The purpose of this study was to quantitatively assess the vertical force distribution (VFD) of subject-specific healthy blue sheep while walking on different slopes using a pressure-sensing walkway. The blue sheep was trained to walk over the pressure-sensing walkway by choosing a comfortable walking speed, and the slope angle increased from 0° to 25°. The sheep's hooves were divided into four quadrants, namely, the cranio-lateral, cranio-medial, caudo-lateral and caudo-medial quadrants, to investigate the VFD of the peak vertical force (PVF), vertical impulse (VI) and occurrence time of the PVF during the stance phase (TPVF). This study demonstrates that the main stressed quadrant of the front hoof changes from the caudo-medial quadrant to the cranio-medial quadrant with increasing slope. The main stressed quadrant of the rear hoof is the cranio-medial quadrant and does not change with the increasing slope. For all the slopes, the vertical force shifted from the lateral quadrant to the medial quadrant and from the caudal quadrant to the cranial quadrant. All the results obtained in the study suggest the feasibility of detecting gait changes in blue sheep, which has potential for the diagnosis of lower limb musculoskeletal diseases in quadrupeds.